Biomechanical Comparison of Three Different Intramedullary Nails for Fixation of Unstable Basicervical Intertrochanteric Fractures of the Proximal Femur: Experimental Studies. (11th December 2018) - Kwak, Dae-Kyung; Kim, Won-Hyeon; Lee, Sung-Jae; Rhyu, Sang-Hyun; Jang, Chul-Young; Yoo, Je-Hyun
Abstract : Objectives . This biomechanical study was conducted to compare fixation stability of the proximal fragments and their mechanical characteristics in proximal femur models of unstable basicervical IT fractures fixed by cephalomedullary nailing using 3 different types of the femoral head fixation. Methods . A total of 36 composite femurs corresponding to osteoporotic human bone were used. These specimens were fixed with Gamma 3 (hip screw type; group 1) in 12, Gamma 3 U-blade (screw-blade hybrid type; group 2) in 12, and proximal femoral nail antirotation-II (helical blade type; group 3) in 12, respectively, and an unstable basicervical IT fracture was created by an engraving machine. After preloading and cyclic loading, the migration of the proximal fragment according to 3 axes was assessed by the stereophotogrammetric method and the migration of screw or blade tip within the femoral head was measured radiographically. Next, the vertical load was continued at a speed of 10 mm/min until the construct failure occurred. Finite element analysis was additionally performed to measure the stress and compressive strain just above the tip of screw or blade within the femoral head. Results . The rotational change of the proximal fragment according to the axis of screw or blade was much greater in group 1 than in groups 2 and 3 (p=0.016 and p=0.007, respectively). Varus collapse was greater in group 3 than in group 2 (p=0.045). Cranial and axial migration of screw or blade within the femoral head were significantly greater in group 3 than in both group 1 (p=0.001 and p=0.002, respectively) and group 2 (p=0.002 and p=0.016, respectively). On finite element analysis, group 3 showed the highest peak von-Mises stress value (13.3 MPa) and compressive strain (3.2%) just above the tip of the blade within the femoral head. Meanwhile, groups 1 and 2 showed similar results on two values. Conclusions . Screw-blade hybrid type and blade type would be more effective in minimizing rotation instability of the proximal fragment in unstable basicervical IT fractures. However, varus collapse of the proximal fragment and cranial and axial migration within the femoral head were greater with blade type than screw-blade hybrid type.